Local, yet global: Implications of caste for MNEs and international business - BAPUJI, Hari (Institutional Knowledge at Singapore Management University, 2023)
Caste is an informal institution that influences socioeconomic action in many contexts. It is becoming increasingly evident that international business research, practice, and policy need to programmatically address caste. To facilitate this endeavour, we review the limited research in IB that has addressed caste, and theorize caste as a distinct informal institution by distinguishing it from systems of stratification like race, class, and gender. In addition, we propose a parsimonious framework to highlight the implications of caste for Indian and non-Indian MNEsin their Indian and global operations. In doing this, we focus on implications with respect to the internal organization and inter-organizational relationships of MNEs, and consider how these implications might differ as based on the MNEs’ organizational forms. We then build on these implications to discuss how MNEs and other stakeholders of international business can address caste inequalities via policies related to human rights, anti-racism, and affirmative action. By bridging theory, practice, and policy, we pave the way for MNEs to address global inequalities that relate to caste.